Role of Glutaraldehyde in Imparting Stability to Immobilized β-Galactosidase Systems - Rukhsana Satar (Brazilian Archives of Biology and Technology, 2018)
ABSTRACT This review article highlights the role of glutaraldehyde as a matrix activator/stabilizer in imparting higher operational and thermal stability to β-galactosidase (βG) for biotechnological applications. Glutaraldehyde has been used extensively as a crosslinking agent as well as for functionalization of matrices to immobilize β-galactosidase. Immobilized β-galactosidase systems (IβGS) obtained as a result of glutaraldehyde treatment has been employed to hydrolyze whey and milk lactose in batch reactors, continuous packed-bed and fluidized bed reactors under various operational conditions. Moreover, these IβGS have also been utilized for the production of galactooligosaccharides in food, dairy and fermentation industries. It was observed that glutaraldehyde provided remarkable stability to immobilize βG against various physical/chemical denaturants, thus enhancing thermal/operational stability and rendering it more suitable for repeated utilization in industrial scale operations.